TraitCapture: genomic and environment modelling of plant phenomic data - Brown, Tim B; Cheng, Riyan; Sirault, Xavier R R; Rungrat, Tepsuda; Murray, Kevin D; Trtilek, Martin; Furbank, Robert T; Badger, Murray; Pogson, Barry J; Borevitz, Justin O (Current opinion in plant biology, 2014)
Agriculture requires a second green revolution to provide increased food, fodder, fiber, fuel and soil fertility for a growing population while being more resilient to extreme weather on finite land, water, and nutrient resources. Advances in phenomics, genomics and environmental control/sensing can now be used to directly select yield and resilience traits from large collections of germplasm if software can integrate among the technologies. Traits could be Captured throughout development and across environments from multi-dimensional phenotypes, by applying Genome Wide Association Studies (GWAS) to identify causal genes and background variation and functional structural plant models (FSPMs) to predict plant growth and reproduction in target environments. TraitCapture should be applicable to both controlled and field environments and would allow breeders to simulate regional variety trials to pre-select for increased productivity under challenging environments.
Keywords: Plants; životní prostředí; Environment; databáze jako téma; Quantitative Trait, Heritable; genomika; Phenotype; Genomics; fenotyp; rostliny; kvantitativní znak dědičný; Databases as Topic